Attosecond Experiments on Plasmonic Nanostructures Principles and Experiments - Schötz, Johannes (BestMasters, 2016)
Johannes Schötz presents the first measurements of optical electro-magnetic near-fields around nanostructures with subcycle-resolution. The ability to measure and understand light-matter interactions on the nanoscale is an important component for the development of light-wave-electronics, the control and steering of electron dynamics with the frequency of light, which promises a speed-up by several orders of magnitude compared to conventional electronics. The experiments presented here on metallic nanotips, widely used in experiments and applications, do not only demonstrate the feasibility of attosecond streaking as a unique tool for fundamental studies of ultrafast nanophotonics but also represent a first important step towards this goal. Contents Electron Scattering in Solids Attosecond Streaking from Metal Nanotips Target Groups Lecturers and students of physics, especially in the area of nanophotonics and attosecond physics About the Author Johannes Schötz received his Master's degree in physics and currently works as a PhD student in the field of ultrafast nanophotonics at the Max Planck Institute of Quantum Optics Garching.